(3GdchGcH GdOQjI aj GdSjQI GdfhQjIs - (3eMeO Hf CHj HcQ Hf CMeO Hf eMeO, CHh GdaVd, HOQ GdOjf GdCSOj GdTGaYj, GdeYQha cSdag HGHf bGVj TgHI,J (B874 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGdc GdeeGdc hehVM GdeSGdc s
(3BNQgG (B:s
(3hgPG BNQ GdJGQjN GdePchQ hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B58 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B30 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B124 s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B((3JGQjN (B262) s
Keywords: (3GdJGQjNs